International research management studies in interdisciplinary methods from business, government and academia - International Conference on the Management of Interdisciplinary Research University of Minnesota) 1986; Birnbaum-More, Philip H.; Rossini, Frederick A.; Baldwin, Donald R. (New York Oxford Oxford University Press, 2011)
A group of papers describing the preconditions, processes, and outcomes of well-managed interdisciplinary research projects from the USA, Canada, Israel, Japan, Brazil, West Germany and Romania.
Conference proceedings.
Electronic reproduction.
Keywords: Interdisciplinary research -- Management -- Congresses; Research -- International cooperation -- Management -- Congresses